Rotigotine treatment partially protects from MPTP toxicity in a progressive macaque model of Parkinson's disease - Scheller, Dieter; Chan, Piu; Li, Qin; Wu, Tao; Zhang, Renling; Guan, Le; Ravenscroft, Paula; Guigoni, Celine; Crossman, Alan R.; Hill, Michael; Bezard, Erwan (Experimental neurology, 2007)
Clinical DA agonist monotherapy trials, which used in vivo imaging of the DA transporter (DAT) to assess the rate of progression of nigrostriatal degeneration, have failed to demonstrate consistent evidence for neuroprotection. The present study aims at reconciling these experimental and clinical data by testing the protective property of the continuously delivered D3/D2/D1 dopamine receptor agonist rotigotine. Using a progressive 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-lesioned (MPTP) macaque model that mimics the progression of Parkinson's disease in vivo ([99mTc]-TRODAT-1 single photon emission computed tomography (SPECT)) and ex vivo ([125I]-nortropane DAT labelling) endpoints were evaluated. After 38 days of treatment followed by two weeks of washout, rotigotine-treated animals were significantly less parkinsonian than the vehicle-treated ones. Such behavioural difference is the consequence of a partial protection of the DA terminals as could be confirmed by ex vivo DAT labelling. However, the protection of nerve terminals was not detected using SPECT. The data suggest that rotigotine exerts partial protection but that conventional imaging would not be able to identify such protection.